Critical Blow-Up and Global Existence for Discrete Nonlinear p-Laplacian Parabolic Equations - Soon-Yeong Chung (Discrete Dynamics in Nature and Society)
The goal of this paper is to investigate the blow-up and the global existence of the solutions to the discrete p-Laplacian parabolic equation utx,t=Δp,wux,t+λux,tp-2ux,t, x,t∈S×0,∞, ux,t=0, x,t∈∂S×0,∞, ux,0=u0, depending on the parameters p>1 and λ>0. Besides, we provide several types of the comparison principles to this equation, which play a key role in the proof of the main theorems. In addition, we finally give some numerical examples which exploit the main results.